The Silent Threat of Non-native Fish in the Amazon: ANNF Database and Review - Doria, Carolina Rodrigues da Costa; Agudelo, Edwin; Akama, Alberto; Barros, Bruno; Bonfim, Mariana; Carneiro, Laís; Briglia-Ferreira, Sylvio Romério; Nobre Carvalho, Lucélia; Bonilla-Castillo, César Augusto; Charvet, Patricia; dos Santos Catâneo, Dayana Tamiris Brito; da Silva, Hugmar Pains; et al. (Frontiers in Ecology and Evolution, 2021)
Non-native fish (NNF) can threaten megadiverse aquatic ecosystems throughout the planet, but limited information is available for the Amazon Region. In this study we review NNF data in the Amazonian macroregion using spatiotemporal records on the occurrence and the richness of NNF from a collaborative network of 32 regional experts, establishing the Amazon NNF database (ANNF). The NNF species richness was analyzed by river basin and by country, as well as the policies for each geopolitical division for the Amazon. The analysis included six countries (Brazil, Peru, Bolivia, Ecuador, Venezuela, and Colombia), together comprising more than 80% of the Amazon Region. A total of 1314 NNF occurrence records were gathered. The first record of NNF in this region was in 1939 and there has been a marked increase in the last 20 years (2000-2020), during which 75% of the records were observed. The highest number of localities with NNF occurrence records was observed for Colombia, followed by Brazil and Bolivia. The NNF records include 9 orders, 17 families and 41 species. Most of the NNF species are also used in aquaculture (12 species) and in the aquarium trade (12 species). The most frequent NNF detected were Arapaima gigas, Poecilia reticulata and Oreochromis niloticus. The current data highlight that there are few documented cases on NNF in the Amazon, their negative impacts and management strategies adopted. The occurrence of NNF in the Amazon Region represents a threat to native biodiversity that has been increasing “silently" due to the difficulties of large-scale sampling and low number of NNF species reported when compared to other South American regions. The adoption of effective management measures by decision-makers is urgently needed and their enforcement needed to change this alarming trend and help protect the Amazon’s native fish diversity.